Sustainable agronomic valorization of unsulfured molasses and defatted soybean meal as an optimized formulation of bio-organic fertilizer enriched with high cell density P-solubilizing bacteria - Mohamad Roslan, Muhamad Aidilfitri; Sohedein, Izzalan; Ling, Puan Sheau; M. Sobri, Zulfazli; Tan, Ali Kee Zuan; Sim, Choon Cheak; Abdul Rahman, Nor Aini (MDPI AG, 2021)
The application of plant beneficial bioinoculants such as phosphate solubilizing bacteria is a sustainable approach to expanding crop performance in agriculture. However, bioinoculant strains, particularly non-sporulating bacteria are often exposed to detrimental conditions throughout the production process and a long period of storage. This will negatively influence their viable cell density and eventually limit its efficacy in the field. To overcome such a scenario, an optimal formulation of biofertilizer should be prioritized. In this report, a sustainable valorization of molasses and defatted soybean meal as formulation of biofertilizer enriched with Enterobacter hormaechei 40a was proposed. Through the two-level factorial design and central composite design, the optimal formulation and fermentation conditions of bio-organic fertilizer to achieve maximum cell density of strain 40a were achieved. The highest cell density of strain 40a in the optimized molasses-DSM (OMD) medium was 12.56 log CFU/mL after 24 h which was 99.7% accuracy towards the predicted value. Interestingly, the solubilized P was increased by 62.4% in the OMD medium (174.07 µg/mL P) as compared to the standard P medium (65.38 µg/mL P). The shelf life of strain 40a after 180 days of storage was improved significantly around 10 log CFU/mL, when the OMD medium was amended with 0.1% sodium alginate. The strategy described here offers opportunities for agronomic formulation and large-scale bio-organic fertilizer production in the agriculture industry.